Single Particle Essays to Determine Heterogeneities within Fluid Catalytic Cracking Catalysts - Nieuwelink, Anne-Eva; Velthoen, Marjolein E Z; Nederstigt, Yoni C M; Jagtenberg, Kristel L; Meirer, Florian; Weckhuysen, Bert M (Chemistry : a European journal, 2020)
Fluid catalytic cracking (FCC) is an important process in oil refinery industry to produce gasoline and propylene. Due to harsh reaction conditions, FCC catalysts are subject to deactivation through for example, metal accumulation and zeolite framework collapse. Here, we perform a screening of the influence of metal poisons on the acidity and accessibility of an industrial FCC catalyst material using laboratory-based single particle characterization that is, μ-XRF and fluorescence microscopy in combination with probe molecules. These methods have been performed on density-separated FCC catalyst fractions, allowing to determine interparticle heterogeneities in the catalyst under study. It was found that with increasing catalyst density and metal content, the acidity and accessibility of the catalyst particles decreased, while their distribution narrowed with catalyst age. For example, particles containing high Ni level possessed very low acidity and were hardly accessible by a Nile Blue dye. Single catalyst particle mapping identifies minority species like the presence of a phosphated zeolite ZSM-5-containing FCC additive for selective propylene formation, catalyst particles without any zeolite phase and catalyst particles, which act as a trap for SO .